Gone so far, yet on the threshold: Nigerian library association at fifty (2012)
In commemoration of the fifty years of the existence of Nigerian Library Association (NLA), this paper goes down the memory lane and takes a critical look at the founding and activities of the NLA as a professional association in the lastfifty years. Relying on published literature and documentary evidence, it, examines the efforts of her founding fathers and successive leadership inputting the Association on a firm footing as a reputable professional association in Nigeria. It notes, in particular, the role of the Association, not only in promoting the welfare and professional development of her members, but also in uplifting the library and information profession and engendering access to information which is a critical resource for national development. It also examines the efforts of the Association in reaching out to other professional bodies in the task of national development in Nigeria as well as fostering co-operation and collaboration with sister associations outside the country for the development of library and information science (LIS) profession at the international level. The paper assesses the performance of the Association over the years based on local minimum standard for professional associations and scores her moderately high. However, applying the benchmark of international best practices, the paper notes some shortcomings in the Association’s performance and concludes that she is still on the threshold. Suggestions on how to move the NLA forward and make her the arrow-head of rapid development in LIS profession in Nigeria are provided.